Effectiveness of the Use of Academic Information Systems (Pinisi Journal of Officers Review, 2024)
The Postgraduate Program of the State University of Makassar has an information system, namely the Academic Information System. This study aims to find out how effective the use of SIA is in employees of the postgraduate program of the State University of Makassar. And whether the existence of SIA in the Postgraduate Program of the State University of Makassar can improve the quality of service to Postgraduate students. Therefore, to achieve this goal, the researcher uses data collection techniques using interview, observation and documentation techniques. The data analysis techniques used in this study are data reduction, data presentation and conclusion and verification. The informants in this study are Mr. Muh Alfian as the Admin of SIA, academic service staff, administrative staff and students. The results of the study show that the use of academic information systems (SIA) in the Postgraduate Program of Makassar State University based on the results of observations, interview results and documentation studies can be effectively reviewed from the system input, system output, processes running with the system and the database used. In this study, several recent indicators related to the results and processes of a system can be used to identify the effectiveness of the use of Academic Information Systems (SIA) in the Postgraduate Program of Makassar State University